2017
DOI: 10.1080/10717544.2016.1259369
|View full text |Cite
|
Sign up to set email alerts
|

Targeting delivery of simvastatin using ICAM-1 antibody-conjugated nanostructured lipid carriers for acute lung injury therapy

Abstract: Acute lung injury (ALI) is a critical illness without effective therapeutic modalities currently. Recent studies indicated potential efficacy of statins for ALI, while high-dose statins was suggested to be significant for attenuating inflammation in vivo. Therefore, a lung-targeted drug delivery system (DDS) delivering simvastatin (SV) for ALI therapy was developed, attempting to improve the disease with a decreased dose and minimize potential adverse effects. SV-loaded nanostructured lipid carriers (SV/NLCs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…The simvastatin nanoparticles (SV‐NPs), a new formulation of simvastatin using nanostructured lipid carriers, were prepared by solvent diffusion method in an aqueous system as described previously . Briefly, 97.5 mg monostearin (Shanghai Chemical Reagent Co., Ltd. Shanghai, China), 30 mg Medium‐chain triglycerides (MCT, Gattefosse, Saint‐Priest, France), 15 mg PEG2000‐stearic acid (Tokyo Kasei Kogyo Co., Ltd., Tokyo, Japan) and 7.5 mg simvastatin were completely dissolved into 0.75 mL ethanol in water bath at 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…The simvastatin nanoparticles (SV‐NPs), a new formulation of simvastatin using nanostructured lipid carriers, were prepared by solvent diffusion method in an aqueous system as described previously . Briefly, 97.5 mg monostearin (Shanghai Chemical Reagent Co., Ltd. Shanghai, China), 30 mg Medium‐chain triglycerides (MCT, Gattefosse, Saint‐Priest, France), 15 mg PEG2000‐stearic acid (Tokyo Kasei Kogyo Co., Ltd., Tokyo, Japan) and 7.5 mg simvastatin were completely dissolved into 0.75 mL ethanol in water bath at 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…Near-infrared DiR fluorescent probe was from Life Technologies (Carlsbad, CA). Octadecylamine-fluorescein isothiocyanate (ODA-FITC) and amino-terminated polyethylene glycol monostearate (NH 2 -PEG 2000 -SA) were synthesized previously [20]. All other solvents were of analytical or chromatographic grade.…”
Section: Methodsmentioning
confidence: 99%
“…The humidified cell incubator was set at 37 °C with 5% CO 2 . To establish in vitro cell model of inflammatory pathological endothelium with over-expressed ICAM-1, the EAs were incubated with 400 ng/mL of LPS for 24 h as our previous study reported [20].…”
Section: Methodsmentioning
confidence: 99%
“…18 The above characteristics offer targets for site-specific delivery and the microenvironment for responsive drug release. To this end, the nanomedicine for ALI has broad alternative therapeutic strategies, including the delivery of anti-inflammatory agents to the disease site, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] the direct scavenging of inflammatory factors, [35][36][37][38][39][40][41][42][43][44][45][46][47] the regulating of inflammatory cell activities, [48][49][50][51][52][53][54][55][56][57][58][59] or the modulating of inflammatory signaling pathways. [60][61][62][63][64][65]…”
Section: Introductionmentioning
confidence: 99%
“…2 To target the endothelium and epithelium, intercellular adhesion molecule-1 (ICAM-1), 87 plateletendothelial cell adhesion molecule (PECAM-1) 88 and surfactant protein (SP) 89 can be bio-conjugated by corresponding antibodies for active targeting nanotherapy. [20][21][22]24,28,35,56,60,63 Nanomedicine can restore barrier integrity and prevent cell death by influencing inflammatory pathways 20,21,44,60,63,65,[70][71][72] and alleviating oxidative stress. 28,35,36,42,54,56 The influence of nanomedicine on cellular architecture can be assessed by a pragmatic optimized air-liquid interface system, which showed comparable results as those in an in vivo study.…”
mentioning
confidence: 99%